p53 in colorectal cancer: from a master player to a privileged therapy target - Sicheng Yan; Fuyuan Zhan; Yuxuan He; Yuehong Zhu; Zhihong Ma (Journal of Translational Medicine)
Abstract Colorectal cancer (CRC) is the third most prevalent malignancy and the second leading cause of cancer-related mortality worldwide. The pathogenesis of CRC primarily stems from the gradual accumulation of genetic mutations, which drive oncogene (e.g., KRAS) activation and tumor suppressor gene (e.g., TP53) inactivation. Loss of genetic stability facilitates the conversion of proto-oncogenes into active oncogenes and the functional impairment of tumor suppressors, collectively propelling CRC progression. The tumor suppressor protein p53, a transcription factor, induces cell cycle arrest, apoptosis, and DNA damage repair under cellular stress, and prevents cancer development by regulating various cellular responses. However, in CRC pathogenesis, TP53 mutations (detected in ~ 74% of cases) subvert these protective mechanisms through dual mechanisms: (i) dominant-negative suppression of wild-type p53 (wt-p53) function, and (ii) acquisition of neomorphic pro-tumorigenic activities, termed gain-of-function (GOF) mutations. New evidence from laboratory and clinical trials shows that some new therapeutic strategies have the potential to treat CRC by reactivating and restoring p53 function, depleting p53 mutants, or targeting p53 with immunotherapy. In this review, we summarize the function of p53 and characterize its mutation in CRC, emphasizing the influence of p53 mutation in the pathogenesis of CRC. In addition, we also describe the current therapeutic strategies for targeting p53 mutants in CRC.